DETERMINATION OF THIAMINE HYDROCHLORIDE AND PYRIDOXINE HYDROCHLORIDE ON RICE WITH WASHING, MILLING AND POUNDING BY SPECTROMETRIC METHODS - Yazid, Edy Agustian; Ati, Damar Pasunaring; Mahardika, Aulia (Journal of Islamic Pharmacy, 2018)
Rice is a principal food source for most of the world's population. Rice has many nutrients including thiamin hydrocloride (THC) and pyrodoxine hydrocloride (PHC). Before consumption, rice is usually processed such as milling, washing, and cooking. Determination of THC on IR-64 and Rojolele rice with washing three times has been conducted. Also determined of PHC on the milled IR-64 rice and the pounded IR-64 rice. The THC was determined by spectrophotometric method at 246 nm. Determination of PHC based on the coupling reaction with diazo reagent in alkaline solution to form azo dye then the absorption was measured at 440 nm. The result of determination of THC on IR-64 and Rojolele rice after washing three times can decrease THC level 12,93% and 12,88% respectively. Determination of PHC on the milled IR-64 rice obtained 1.54 Â± 0.027 mg/g and on the pounded IR-64 rice 1.80 Â± 0.048 mg/g. The result of statistical test with independent T test showed there were significant difference (Î± = 0,05) PHC level on both treatments.